Airside Capacity Utilization in a Nigerian Airport: A Case Study of Murtala Muhammed International Airport - M. S, Stephens,; O.T, Ayo Agunbiade (American International Journal of Multidisciplinary Scientific Research, 2019)
Airport Capacity generally refers to the ability of an airport to handle a given volume of traffic (demand) and should be assess to ensure they are adequate for lay down Standards. This study was based on the assessment of Airside Capacity Utilization at an International Airport; the Runway is the focus of this study. Capacities are very important and this dictates the level of patronage made by airlines at the Airport. Murtala Mohammed International Airport (MMIA) as a case study was examined; the domestic and international traffic flow well assessed on a daily basis, over a period of sixteen (16) years, to determine the traffic intensity of the airport was obtained from Federal Aviation Authority of Nigeria (FAAN) and Nigerian Airspace Management Agencies (NAMA). This experimental research involved the estimation of the traffic flow, installed capacity of the Runway, the intensity of traffic on hourly, daily, monthly bases. The model adopted for the research was Queue Theory. Findings show that the domestic wing generates more traffic flow than international wing of the Runway. The through put at the Runways shows that the runway is adequately utilized to accommodate existing traffic, expansion in the form of construction will not be necessary.